Integration of Community Activities in The Public Space as a Learning Resource on Social Studies - Jumriani Jumriani; Muhammad Muhaimin; Ersis Warmansyah Abbas; Muhammad Rezky Noor Handy; Mutiani Mutiani (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Integration of community activities as a source of social studies learning is essential. This is so that learning is not only focused on planting concepts. However, this integration is expected to produce learning outcomes in the form of understanding concepts and their relation to the context of everyday life. Community activities can be found in a public space. One of them is a public space in Banjarbaru City, which is known as the Taman Pintar. Therefore, this study aims to identify public spaces in the Taman Pintar as a source of social studies learning. A qualitative approach is used in this study to explain a phenomenon as profoundly as possible by collecting data. The research instrument is the researcher himself—data collection techniques in observation, interviews, and documentation. Data analysis begins with data collection, reduction, presentation, and conclusion drawing. The data validity test used is source triangulation, technique triangulation, and time triangulation. Finally, extended observations were made to complete the incomplete data. Research results in three parts of the people's activity social activities in Taman Pintar: social, economic, and government. Therefore, social studies teachers are expected to prepare contextual learning processes or include social studies learning with learning resources in the form of community social activities in the Taman Pintar area as social studies learning resources.